Public policy and devolved governance: Facilitating the social and solidarity economy in the Liverpool City Region - Helen Heap; Alan Southern; Matt Thompson (United Nations Research Institute for Social Development (UNRISD), 2020)
National policy support in the United Kingdom for the social and solidarity economy is complex, often caught between central and local interventions, both direct and indirect. According to the authors, there has been legislation, underpinned by an ideology of business deregulation and a more enterprising mindset, that has stimulated a very particular idea of the social economy at the national level. At the same time, two further pieces of legislation have impacted local-level SSE: the Public Services (Social Value) Act 2012, which required public service providers to consider economic, social and environmental value in their procurement decisions, and thus provided opportunities for local governments to support the SSE; and the Cities and Local Government Devolution Act 2016. The authors discuss the importance of devolution for the SSE in the Liverpool City Region. The SSE has been recognized as an important part of efforts to build a more inclusive economy. The Metro Mayor considers the SSE a necessary partner in achieving city-region objectives, and the Combined Authority has implemented new means of collaboration. New governance arrangements have produced a political voice for the sector through the Liverpool City Region SSE Reference Panel. Collaboration has also led to a finance initiative that delivers better forms of social investment into the sector. Overall, however, the authors conclude that the UK remains a highly centralized state and much remains to be done to face the needs that exist in the city region - both the needs of communities, and the help required to ensure the development and successful growth of the SSE.
Keywords: 330; Sozialwirtschaft; Politik; Soziale Werte; Liverpool